Long-term outcomes of cytokine therapy in pregnant women with cervical intraepithelial neoplasia - Yu.E. Dobrokhotova; E.I. Borovkova; V.V. Romanovskaya; I.V. Stepanyants (LCC «Medicine-Inform», 2022)
Yu.E. Dobrokhotova1, E.I. Borovkova1, V.V. Romanovskaya1, I.V. Stepanyants2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Maternity Hospital of the City Clinical Hospital No. 40, Moscow, Russian Federation Aim: to assess long-term outcomes of exogenous cytokine therapy in pregnant women with cervical intraepithelial neoplasia (CIN). Patients and Methods: this prospective study included 50 pregnant women with CIN. Women were randomized into two groups. Group 1 women (n=30, mean age 31.6±1.7 years) received vaginal suppositories with Superlymph 25 U. Group 2 women (n=20, mean age 29.8±1.4 years) received rectal suppositories with Superlymph 25 U. Cervical smear cytology (at baseline, 22 days after starting treatment, and 6 weeks after delivery), colposcopy, and cervical biopsy (at baseline and 6 weeks after delivery) were performed. Results: in group 1, cytology revealed high-grade squamous intraepithelial lesion (HSIL) in 43.3%, atypical squamous cells-cannot exclude a high-grade lesion (ASC-H) in 6.7%, and atypical squamous cells of undetermined significance (ASCUS) in 10%. In group 2, cytology revealed low-grade squamous intraepithelial lesion (LSIL) in 25%, HSIL in 45%, ASC-H in 10%, and ASCUS in 20%. After the treatment course, in group 1, a regress from HSIL to LSIL was detected in 6.7%, regress from LSIL to ASCUS in 3.3%, and regress from HSIL to ASC-H in 3.3%. In group 2, NILM was detected in 5%, a regress from HSIL to LSIL in 5%, and regress from LSIL to ASCUS in 5%. Histologically, LSIL was verified in 50% of women of both groups, CIN grade 2 in 36.7% (group 1) and 40% (group 2), CIN grade 3 in 13.3% (group 1) and 10% (group 2). Six weeks after delivery, cytological abnormalities were identified in 30 women of both groups (HSIL in 56.7% and LSIL in 43.3%). Histology detected  carcinoma in situ in 3.3% and CIN grade 2-3 in 53.3%. Delivery in time (on average, at 38.4±1.1 weeks of gestation) occurred in all women. Conclusion: trend toward the improvement of cytological parameters irrespective of the mode of drug administration is reported after finishing cytokine therapy. Normalization of cytological findings was reported in 3.3% (group 1) and 5% (group 2), while improvement was reported in 6.6% (group 1) and 10% (group 2). No worsening was reported. Keywords: cytokine therapy, pregnancy, cervical intraepithelial neoplasia, cytological study, histological study. For citation: Dobrokhotova Yu.E., Borovkova E.I., Romanovskaya V.V., Stepanyants I.V. Long-term outcomes of cytokine therapy in pregnant women with cervical intraepithelial neoplasia. Russian Journal of Woman and Child Health. 2022;5(2):106-111 (in Russ.). DOI: 10.32364/2618-8430-2022-5-2-106-111.